PARP inhibitors in melanoma treatment: potential, challenges, and future directions - Anaeme, Angela; Moussa, Karen; Mansour, Abdallah N.; Nassief, George; Ansstas, George (Frontiers in Oncology, 2025)
Genome integrity is a critical driver of cellular stability, and defects in the processes that maintain genome health are potent sources of cancer progression. Homologous recombination deficiency (HRD), which damages cells through absent or erroneous repair of double-stranded DNA breaks, is a prime example of such cellular dysfunction. Poly(ADP-ribose) polymerase (PARP) inhibitors exploit these aberrancies in the cellular repair process by arresting the ability of the PARP enzyme to repair cellular and genetic damage, inducing the accumulation of DNA damage and cancer cell death. While the utility of PARP inhibitors has been established in many HRD-associated tumors — particularly breast, pancreatic, ovarian, and prostate cancer — less robust evidence exists for the efficacy of PARP inhibitors in melanoma. Increasing efforts are underway to investigate PARP inhibitors as a viable treatment option for advanced and metastatic melanoma, both as monotherapy and in combination with other agents such as immune checkpoint inhibitors and BRAF/MEK inhibitors. Though several gaps in our knowledge of the use of PARP inhibitors in melanoma still exist, promising headway is being made in our understanding of its efficacy and safety. Here, we present a review of the utility of PARP inhibitors in melanoma, current clinical trials, and future avenues for further exploration.